Respuesta :
Answer:
x= ½, y= 7
Step-by-step explanation:
[tex]\textcolor{steelblue}{\text{\textcircled{1} Label the equations}}[/tex]
6x -y= -4 -----(1)
2x +2y= 15 -----(2)
[tex]\textcolor{steelblue}{\text{\textcircled{2} Make y the subject of formula}}[/tex]
We could also make x the subject of formula in one equation, however the equation can be easily rearranged so that the coefficient of y is 1. This can be done by moving the y term to the right hand side of the equation, and the rest to the left. Note that each time you bring a term or constant over to the other side of the equation, its sign changes (e.g. positive to negative).
From (1):
6x +4= y
y= 6x +4 -----(3)
Label the equation as equation (3) so we can refer to it easily later.
[tex]\textcolor{steelblue}{\text{\textcircled{3} Substitute (3) into (2)}}[/tex]
Now that we have an equation of y that is written in terms of x, we can replace all the y in equation (2) so that the whole equation is only in terms of x.
Subst. (3) into (2):
2x +2(6x +4)= 15
Expand:
2x +12x +8= 15
Simplify:
14x +8= 15
14x= 15 -8
14x= 7
x= 7 ÷14
x= ½
[tex]\textcolor{steelblue}{\text{\textcircled{4} Find y}}[/tex]
Substitute x= ½ into (3):
y= 6(½) +4
y= 3 +4
y= 7